Analisis Kemampuan Berpikir Kritis Siswa Dalam Menyelesaikan Masalah Materi Program Linear Ditinjau Dari Gaya Kognitif Field-Dependent dan Field-Independent - zahro, Solikhati; Zuhri, Zainullah (Discovery, 2024)
The aim of this research is to describe students' critical thinking abilities in solving problems with linear programming material in terms of Field-Dependent and Field-Independent cognitive styles. The type of research used is descriptive research with a qualitative approach. The research instruments used in this research include the cognitive style test (GEFT test), critical thinking ability test, and interview guide. The subjects used in this research were 4 students taken from class XI of Dewantoro Purwosari Vocational School. According to the results of the GEFT test that was carried out, the subject was 2 students with a Field- Dependent cognitive style and 2 students with a Field-Independent cognitive style. The information retrieval techniques used in this research are the GEFT test, critical thinking ability test, and interview guide. Next, the data collection technique used is reducing data, presenting data and drawing conclusions. At the stage of checking the validity of the data, this research used triangulation techniques, namely tests and interviews. The results of this research state that students who have a Field-Dependent cognitive style have quite high critical thinking abilities. And able to fulfill 3 indicators of critical thinking ability including the analysis stage, evaluation stage and inference stage (conclusion). Meanwhile, the subject interpretation stage FD1 is classified as sufficient, while FD2 is classified as not yet sufficient. Meanwhile, students who have a Field- Independent cognitive style have high critical thinking abilities. And able to fulfill 4 indicators of critical thinking ability including the interpretation stage, analysis stage, evaluation stage and inference stage (conclusion).